2012
DOI: 10.1155/2012/363058
|View full text |Cite
|
Sign up to set email alerts
|

Cogasification of Coal and Biomass: A Review

Abstract: Recently, there has been significant research interest in cogasification of coal and various types of biomass blends to improve biomass gasification by reducing the tar content in the product gas. In addition, ash present in biomass catalyzes the gasification of coal. However, due to the fibrous nature of biomass and the large difference in gasification temperature of coal and biomass, cogasification in existing systems presents technical challenges. This paper documents research studies conducted on the cogas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 41 publications
1
50
0
2
Order By: Relevance
“…Considerou-se na simulação um gaseificador de leito fluidizado pois é um dos reatores mais utilizados na indústria em processos de CM e biomassa segundo (BRAR et al, 2012). As especificações do gaseificador foram baseadas em um modelo comercial leito fluidizado modelo High Temperature Winkler (HTW™) do fabricante ThyssenKrupp, que opera com 1,6 a 30 t/h de combustível, produzindo de 3000 a 34000 Nm³/dia de gás (MELO, 2016), no caso de CM.…”
Section: Congresso Brasileiro De Engenharia Química Em Iniciação unclassified
“…Considerou-se na simulação um gaseificador de leito fluidizado pois é um dos reatores mais utilizados na indústria em processos de CM e biomassa segundo (BRAR et al, 2012). As especificações do gaseificador foram baseadas em um modelo comercial leito fluidizado modelo High Temperature Winkler (HTW™) do fabricante ThyssenKrupp, que opera com 1,6 a 30 t/h de combustível, produzindo de 3000 a 34000 Nm³/dia de gás (MELO, 2016), no caso de CM.…”
Section: Congresso Brasileiro De Engenharia Química Em Iniciação unclassified
“…In the specific case of co-gasification processes, water, CO2 and oxygen are introduced to carry out all the gasification reactions [9,35]. Therefore, in 4-end mode, flue gases from the boiler or gasification unit ( Figure 3) could be used as sweep to achieve a high OTM integration degree in the co-gasification process.…”
Section: Integration Of Otm Modules In Gasification Processesmentioning
confidence: 99%
“…Zhou (2014) presented a review of synergy effects during co-gasification in several experimental studies. Brar et al (2012) and Emami-Taba et al (2013) presented a comprehensive review of recent progress in coal-biomass co-gasification technologies. Different types of chemical reactors are used in co-gasification such as entrained-flow, fixed-bed and fluidized-bed gasifiers.…”
Section: Introductionmentioning
confidence: 99%
“…According to Emami-Taba et al (2013), fluidized-bed gasifiers are the most used ones. Brar et al (2012) pointed out that the operating temperature of gasifiers ranges from 850 to 1000 ºC, with a maximum temperature limit established to avoid ash sintering. The authors also observed that gasifiers operate from atmospheric pressure up to 20 bar.…”
Section: Introductionmentioning
confidence: 99%